Fathers’ caregiving time before and after the COVID-19 pandemic - Lee T. Gettler; Sarah Hoegler Dennis; Stacy Rosenbaum; Sonny Agustin Bechayda; Christopher W. Kuzawa (PLoS ONE, 2026)
The COVID-19 pandemic contributed to greater day-to-day time spent together for many families. Some research in Euro-American settings indicated that fathers spent more time caring for their children during the pandemic than previously, with the potential for lasting effects on fathers’ caregiving. However, there are few longitudinal studies with post-pandemic paternal care data and analyses from non-Euro-American contexts. We drew on a large sample of men (N = 649; Obs. = 1286) enrolled in a longitudinal study in the Philippines with waves of data collection prior to the pandemic in 2009 (wave 1) and 2014 (wave 2) and a third wave post-pandemic in 2022−23 (wave 3). Our main analyses focus on within-individual change in paternal caregiving for men residing with young children (N = 307) from the pre-pandemic (wave 2) to post-pandemic period (wave 3). Fathers showed meaningful within-individual declines in routine (intensive) caregiving time from the pre-pandemic (wave 2) to the post-pandemic (wave 3). However, they reported comparable engagement in overall, recreational, and educational care post-pandemic relative to their pre-pandemic levels at wave 2. Men’s shifts in pre-to-post-pandemic employment status predicted their changes in caregiving time, particularly for educational care. The post-pandemic patterns we observed for educational care are potentially consistent with shifting dynamics for fathers’ caregiving in this domain following the pandemic and complement results elsewhere connecting fathers’ employment characteristics to their caregiving during and after the pandemic.